TRANSLATION TECHNIQUE AND TRANSLATION METHOD FRAMEWORKS: A COMPARATIVE ANALYSIS WITHIN TRANSLATION STUDIES - Gunawan Tambunsaribu (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
This study examines the similarities and distinctions between translation methods and translation techniques to clarify their conceptual relationship in translation studies. Because these terms are frequently used interchangeably or ambiguously in the literature, the study establishes clearer conceptual boundaries and contributes to greater theoretical precision. Employing a qualitative comparative design through document analysis, the research analyzes 2 translation frameworks, translation methods proposed by Newmark and translation techniques proposed by Molina and Albir, to systematically compare the two concepts. The analysis identifies five major areas of similarity: orientation toward source language (SL) preservation, orientation toward target language (TL) naturalness, treatment of culture-specific elements, emphasis on meaning transfer rather than formal equivalence, and flexibility through translator intervention. The findings also demonstrate that, despite these shared characteristics, translation methods and translation techniques differ fundamentally in their analytical scope and function. Translation methods operate at the macro level, guiding the overall approach to an entire text, whereas translation techniques function at the micro level, addressing specific translation problems within individual linguistic units. This distinction advances existing knowledge by providing a more systematic conceptual framework for differentiating the two constructs while explaining their complementary roles in translation decision-making. The study is limited to a comparative analysis of theoretical literature and does not evaluate the application of methods and techniques in empirical translation practice.